PENETAPAN KADAR ASAM BORAT DAN ZINK SULFAT DALAM OBAT TETES MATA DENGAN CARA MIKROTITRASI - Fitrileni
Abstract: Methods of quantitative analysis for boric acid and zink sulphate in an opthalmic solution by secondary coulometric and potensiometric titration were studied. The end point of coulometri method for boric acid in opthalmic solution was determined based on the pH of the equivalent point and the theoretical time of titrant generation. Manitol was added to the precusor solution. The recovery was 100.64 ± 1,86%. The quantitation limit of this method was 1 µmot Zinc sulphate couldnot be determined by coulometric titration because the reaction of zinc ion with ethylendiamineacetate is disturbed by the reaction at the anode of generator electrode which could not be separated yet. Thereafter, zinc sulphate was determined in acetate buffer solution of pH 4.6 by complexometric microtitration with the end point determined by potentiometry. The result showed that the recovery was 95.41 ± 4.55 %. The quantitative limit this method was 10 µmol.